TiO2 nanoparticle-supported Ni catalyst for the dehydrogenation of hydrazine hydrate. (February 2023) - Liu, Ying; Liu, Xiaoya; Liu, Xinying; Li, Yajing; Ma, Jinghuan; Ma, Cong
Abstract: As one of the key factors that affect the application of hydrazine hydrate as a potential hydrogen source, efficient and cheap catalyst is particularly important. Nickel based catalysts have been widely studied because of their excellent catalytic performance for the decomposition of hydrazine hydrate to hydrogen. Herein, a Ni catalyst supported on anatase TiO2 through reduction and impregnation methods was prepared. Structure of the catalyst was investigated by transmission electron microscopy (TEM), X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET), and X-ray photoelectron spectroscopy (XPS). The effects of the amount of TiO2 and the concentration of NaOH on the activity of the catalyst were investigated. The results showed that the catalyst prepared with a metal nickel content of 0.2 mmol using 100 mg of the nano-TiO2 support had the best catalytic performance. Hydrazine hydrate could be completely decomposed at 343 K in 2.83 min, the hydrogen selectivity attained 100%, and the turnover frequency (TOF) value was 265.49 h −1 . In this catalyst, transition metal Ni was dispersed on the support surface in the form of amorphous elemental or oxide. Anatase TiO2 support had the advantages of promoting the dispersion of metal Ni, exposing the active site, changing the electronic state of the active center, strengthening the strong metal-support interaction (SMSI), and improving the activity of the catalyst. After ten cycles of use, the performance of the catalyst stabilized and the hydrogen selectivity was still as high as 100%. Highlights: TiO2 supported amorphous Ni nanoparticles as a non-noble metal catalyst was prepared. The Ni/TiO2 catalyst was applied for dehydrogenation of hydrous hydrazine. The Ni/TiO2 catalyst showed 100% H2 selectivity, TOF value of 265.49 h −1 .